The Influence Tax Avoidance, Cash Flow Volatility and Capital Expenditure Toward Cash Holding In Pharmaceutical Sub-Sector Consumer Goods Industry Listed at Indonesia Stock Exchange - Jessica (Outline Publisher, 2022)
This study aims to determine the influence of Tax Avoidance, Cash Flow Volatility and Capital Expenditure toward Cash Holding in pharmaceutical sub-sector consumer goods industry listed at Indonesia Stock Exchange. This research is based on quantitative data type and the data source is from secondary data. The unit analysis and observation in this study pharmaceutical sub-sector consumer goods industry listed at Indonesia Stock Exchange, with a total population of 10 companies. From this population, 5 companies are chosen by purposive sampling technique throughout 8 periods of time, specifically from 2014 – 2021 which sum up to 40 samples. The method of analysis used in this study is multiple linear regression analysis. This analysis includes descriptive statistics, classical assumption test, multiple regression analysis, hypothesis testing through t and F test, and coefficient of determination test. The result of the t-test indicate that the Tax Avoidance has a significant effect on Cash Holding, Cash Flow Volatility has no effect and not significant on Cash Holding, and Capital Expenditure has no effect and not significant on Cash Holding. The result of the F test indicate that Tax Avoidance, Cash Flow Volatility and Capital Expenditure have a significant effect on Cash Holding.